Investigation of the effect of Reynolds number on laminar separation bubbles on controlled-diffusion compressor blades in cascade - Schnorenberg, David G. (Monterey, California. Naval Postgraduate School, 2012)
Approved for public release; distribution is unlimited === Detailed experimental investigation of second generation, controlled diffusion, compressor stator blades at an off-design inlet flow angle was performed in a low speed cascade wind tunnel using various experimental procedures. The objective of the study was the characterization of the off-design flow and the detailed investigation of flow separation which occurred near midchord. When it was found that the flow separation behavior was strongly influenced by the Reynolds number, the effect of Reynolds number variation on flow separation was investigated. Surface flow visualization was performed to gain general insight into the flow behavior. Blade surface pressure measurements were obtained using instrumented blades, from which coefficients of pressure were calculated. Laser Doppler velocimetry (LDV) was used to characterize the off-design flow upstream, in the passage between two blades, in the boundary layer on the suction side of the blades, and in the wake region. Overall, good comparisons between blade surface pressure measurements, LDV data and flow visualization were obtained for the separation region. At the highest Reynolds number, separation was turbulent and three dimensional and at the low Reynolds number the separation was predominately laminar and two dimensional.